Mitigating hospital-onset Clostridioides difficile: The impact of an optimized environmental hygiene program in eight hospitals. (20th March 2023) - Carling, Philip C.; O'Hara, Lyndsay M.; Harris, Anthony D.; Olmsted, Russell
Abstract: Objective: To evaluate the impact of a standardized, process-validated intervention utilizing daily hospital-wide patient-zone sporicidal disinfectant cleaning on incidence density of healthcare-onset Clostridioides difficile infection (HO-CDI) standardized infection ratios (SIRs). Design: Multi-site, quasi-experimental study, with control hospitals and a nonequivalent dependent variable. Setting: The study was conducted across 8 acute-care hospitals in 6 states with stable endemic HO-CDI SIRs. Methods: Following an 18-month preintervention control period, each site implemented a program of daily hospital-wide sporicidal disinfectant patient zone cleaning. After a wash-in period, thoroughness of disinfection cleaning (TDC) was monitored prospectively and optimized with performance feedback utilizing a previously validated process improvement program. Mean HO-CDI SIRs were calculated by quarter for the pre- and postintervention periods for both the intervention and control hospitals. We used a difference-in-differences analysis to estimate the change in the average HO-CDI SIR and HO-CAUTI SIR for the pre- and postintervention periods. Results: Following the wash-in period, the TDC improved steadily for all sites and by 18 months was 93.6% for the group. The mean HO-CDI SIRs decreased from 1.03 to 0.6 (95% CI, 0.13–0.75; P = .009). In the adjusted difference-in-differences analysis in comparison to controls, there was a 0.55 reduction (95% CI, −0.77 to −0.32) in HO-CDI (P < .001) or a 50% relative decrease from baseline. Conclusions: This study represents the first multiple-site, quasi-experimental study with control hospitals and a nonequivalent dependent variable to evaluate a 4-component intervention on HO-CDI. Following ongoing improvement in cleaning thoroughness, there was a sustained 50% decrease in HO-CDI SIRs compared to controls.